A practical inflammatory blood-cell marker for cardiovascular risk stratification in psoriasis: Development of the Platelet-Leukocyte Adjusted Cardiovascular (PLAC) score - Julian A. Cortes; Shaliz Aflatooni; Andrea Ure; Gabriela Palma; Nicole Johnsen; Kimberly Smart; Yvonne Nong; April W. Armstrong (PLoS ONE, 2026)
Background Psoriasis is an inflammatory disease associated with atherosclerotic cardiovascular disease (ASCVD). Although blood-cell markers predict ASCVD in the general population, the utility of these markers in cardiovascular risk stratification in psoriasis remains unclear given heightened inflammatory burdens among these patients. Objectives We aimed to develop a composite ASCVD risk score for psoriasis and evaluate its performance by integrating a novel inflammatory blood-cell marker with traditional cardiovascular risk factors. Methods We conducted a retrospective cohort study using All of Us (enrollment:May 2018-October 2023). ASCVD included acute coronary syndrome, cerebrovascular accident, or coronary artery disease. Independent predictors of ASCVD in Cox regression informed the Platelet-Leukocyte Adjusted Cardiovascular (PLAC) score, incorporating the Neutrophil-to-Platelet-to-Monocyte Ratio (NuPMoR=neutrophils/[platelets x monocytes]), age ≥ 65, male sex, hypertension, and diabetes. Results Among 1,572 psoriasis patients (median follow-up 7.2 years), the PLAC score (AUC 0.69, 95% CI 0.65–0.74), which incorporates NuPMoR, stratified patients into low-, medium-, and high-risk groups with corresponding 10-year ASCVD incidences of 4.9%, 11.8%, and 39.9%. Compared with the low-risk group, medium- (HR 2.27, 95% CI 1.53–3.39) and high-risk (HR 6.40, 95% CI 3.97–10.33) groups had significantly higher ASCVD hazard. The PLAC score demonstrated similar or numerically higher discrimination than the Framingham and PCE models in limited samples. Conclusions The PLAC score is a practical, psoriasis-specific ASCVD risk tool that integrates a novel inflammatory marker with traditional risk factors. It enables clinically meaningful ASCVD risk stratification using routine laboratory values in a high-risk population and may help identify psoriasis patients warranting closer cardiovascular monitoring.